Customer protection of digital services by commercial banks concerning consumer and community protection in the financial services sector - Usanti, Trisadini; Setiawati, Anindya (Trigin Publisher, 2024)
In this digital era, banks must adjust themselves, given the needs of customers who want rapidity and flexibility of banking services so that customers can quickly and safely anytime, anywhere. Almost all commercial banks have digital services, but on the other hand, there are potential risks that will be faced. The problems discussed in this study are the potential risks in digital services and risk management related to the protection of customer rights. The approaches used in this research include statutory and conceptual approaches. The result of this research is that the main risks faced in digital services are operational risk, strategic risk, and reputation risk. So preventive efforts by conducting risk management and ensuring information system security and cyber resilience for Consumer Protection. While repressive protection with a handling mechanism for any questions and / or complaints from consumers. It is emphasized in POJK 22/2023 that banks such as PUJK are required to have and implement a mechanism for handling complaints submitted by consumers. Banks are required to provide consumer complaint services whose scope consists of receiving complaints, handling complaints, and resolving complaints.